Diplycosia rigidifolia sp. nov. (Ericaceae) from Borneo, Sabah, Malaysia. (30th August 2016) - Fritsch, Peter W.; Bush, Catherine M.
Abstract : Diplycosia rigidifolia sp. nov. from Mount Kinabalu, Borneo, Sabah, Malaysia, is described and illustrated. This species is similar to D. urceolata, but differs by its shorter petiole, thicker, strictly elliptic leaf blades, longer pedicels, calyx lobes with sharply acuminate apex, and larger purplish black fruiting calyx. The species is known only from Mt Kinabalu in northern Sabah state, Malaysia.